The Impact of Distributed Zakat on Sustainable Economic Development in Indonesia: A VECM Approach - Hamadou, issa; Jallow, Mamadou Salieu (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2024)
This paper aims to look at the effect of distributed zakat on sustainable economic development variables in Indonesia. Particularly economic growth, human development index (HDI), and poverty rate. A vector error correction model (VECM) was used with time series data from 2001–2020. Furthermore, Unit root test and co-integration test have been also applied for testing the stationarity and long run relationship respectively. It was assumed in the study that there is an affirmative impact of distributed zakat on sustainable economic development in short and long run. Consequently, the primary objectives of zakat distribution related to sustainable zakat funds and economic growth will be successfully achieved. One of the limitations of this research is the case study of one country, Indonesia, so it is suggested to include more countries in further studies in order to generalize the results. Indonesian government should implement tax reduction policies for zakat institutions to assist them in optimizing collection and distribution schemes. In addition, zakat institutions are also recommended to expand their distribution to reach people that are more vulnerable so that it could have a crucial impact on poverty alleviation and enhance sustainable development. There is no sufficient empirical results related to zakat and SDGs. However, the present paper is original and assessed the dynamic short-run and long run effect of distributed zakat on the Human Development Index (HDI), poverty rate and economic growth in Indonesia.